The F-index and coindex of V-Phenylenic Nanotubes and Nanotorus and their molecular complement graphs - Alsharafi, Mohammed S. Y.; Alameri, Abdu Q. (ST PETERSBURG NATL RESEARCH UNIV INFORMATION TECHNOLOGIES, MECH & OPTICS, 2021)
The forgotten topological index was defined to be used in the analysis of chemical structures which often appear in drug molecular graphs. In this paper, we studied the F-index and F-coindex for certain important physico chemical structures such as V-Phenylenic Nanotube V PHX[m, n] and V-Phenylenic Nanotorus V PHY [m, n] and their molecular complement graph. Moreover, we computed F-polynomial of the V-Phenylenic Nanotubes and Nanotorus. These explicit formulae can correlate the chemical structure of molecular graphs of Nanotubes and Nanotorus to information about their physicochemical structure.
Keywords: F-index; F-coindex; V-Phenylenic Nanotubes and Nanotori; molecular graph; molecular complement graph; 2ND ZAGREB INDEXES; 1ST; Science & Technology - Other Topics